UJI EFEKTIVITAS SARI BUAH KURMA (Phoenix dactylifera) TERHADAP GAMBARAN HISTOPATOLOGI GASTERMENCIT JANTAN (Mus musculus L) YANG DIBERI ASPIRIN - BUNGA PUTRI AYUNIRRAHIM; YENITA YENITA (JURNAL ILMIAH MAKSITEK, 2023)
Date palm juice (Phoenix dactylifera) isProcessed products from dates, which have various contents that are beneficial for health. Research has been carried out to test the effectiveness of date palm juicewhich aims to determine the effectiveness of date palm juice on the gastric histopathological picture of male mice (Mus musculus L) given aspirin. Method:This research is an experimental study with a research design of "Post test only control group design" and "Simple randomized sampling". Using 35 male mice aged 2-3 months weighing 20-30 grams were divided into 5 groups randomly. Negative control group, positive control group, and treatment group (I, II, III) dose of 7 mg/kgBW, 14 mg/kgBW, 21 mg/kgBW.Aspirin and date juice were given for 10 days with an interval of 1 hour, then histopathological examination of the ulcer score was carried out. Results:The effectiveness of date fruit juiceIn inhibiting gastric damage of male mice (Mus Musculus L), each group was tested for Chi Square test statistics.The results of statistical tests showed that date palm juice at a dose of 7 mg/kgBW, 14 mg/kgBW, 21 mg/kgBWdwas able to inhibit gastric damage of male mice that were given aspirin, the result was p<0.05. From the results of the study that date palm juice was effective as a therapy, in the stomach of mice given aspirin, according to the results of the data analysis of the gastric histopathological description of male mice, p < 0.05.PDate palm juice (Pheonix dactylifera) can inhibit gastric damage in mice, especially at a dose of 21 mg/kgBW.